The role of molecular vibration in nanosecond repetitively pulsed discharges and in DBDs in hydrogen plasmas. (18th July 2016) - Colonna, G; D'Ammando, G; Pietanza, L D
Abstract: A self-consistent state-to-state model of pure hydrogen has been used to investigate the development of nanosecond repetitively pulsed discharges and dielectric barrier discharges, the latter coupling the kinetic model with an equation for the circuit, thus mimicking an insulated electrode with an external capacitance. Vibrationally excited states play a fundamental role, affecting the degrees of dissociation and ionization, as well as internal and free-electron distributions.